Iceland : Fifth Review Under the Stand-By Arrangement, and Request for Modification of Performance Criteria and Rephasing of Access-Staff Report; Informational Annex; Staff Statement; Press Release on the Executive Board Discussion; and Statement by the Executive Director for Iceland. (IMF Staff Country Reports; Country Report ;, 2011)
The paper describes the impressive economic progress made by Iceland in implementing program policies, stabilizing the exchange rate, and bringing inflation down, under a program supported by a Stand-By Arrangement (SBA). The authorities noted that key challenges are to reduce the high level of unemployment, lift capital controls, accelerate private sector debt restructuring, and strengthen financial sector supervision and regulation. The full implementation of the economic program will create favorable conditions for economic progress based on sustainable public finances, private enterprise, and free markets.